2019
DOI: 10.1186/s41231-019-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of herpes simplex, varicella zoster and Cytomegalovirus in tumorous and adjacent tissues of patients, suffering from colorectal cancer in Iran

Abstract: Background: Colorectal cancer (CRC) can be considered as a result of multiple risks factors, and the significant role of infectious ones, especially viral diseases could not be underestimated. Despite endorsed attempts to identify the accelerating effects of different herpes viridea, such as HSV-1, HSV2, VZV and CMV on the deterioration of different kinds of malignancy, the relationship between these viruses and CRC have not successfully been understood. Taking advantages of these facts, we assessed the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…On the other hand, epidemiological studies based on diverse techniques do not attribute a major role in the etiology of CRC to any human herpesvirus, regardless of their presence in clinical samples [47][48][49]. In accordance with these findings, serological tests showed no significant differences of antibodies against human herpesviruses between CRC patients and controls [50].…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, epidemiological studies based on diverse techniques do not attribute a major role in the etiology of CRC to any human herpesvirus, regardless of their presence in clinical samples [47][48][49]. In accordance with these findings, serological tests showed no significant differences of antibodies against human herpesviruses between CRC patients and controls [50].…”
Section: Discussionmentioning
confidence: 66%
“…Infection with HSV has been shown to induce esophagitis but the association between HSV and EC needs further investigation. Based on the results of a case-control study performed on 88 paraffin-embedded tissues from CRC patients in Tehran, Iran, no association between this type of cancer was found with HSV and CMV infections 10) . Considering that HSV-DNA was observed in three control samples isolated from tissues adjacent to the neoplastic tissue, it has been suggested that HSV can kill tumor cells and reduce the progression of CRC 10) .…”
Section: Cmv-hsv Virusmentioning
confidence: 99%
“…Based on the results of a case-control study performed on 88 paraffin-embedded tissues from CRC patients in Tehran, Iran, no association between this type of cancer was found with HSV and CMV infections 10) . Considering that HSV-DNA was observed in three control samples isolated from tissues adjacent to the neoplastic tissue, it has been suggested that HSV can kill tumor cells and reduce the progression of CRC 10) . A study in an area with a high prevalence of EC in North Africa found that EC was not associated with CMV 33) .…”
Section: Cmv-hsv Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Infections Prolonged or untreated infections can also lead to GI cancers. Human papillomavirus, [30] Epstein-Barr virus, [31] Herpes simplex 1 virus [32] and cytomegalovirus [33] are associated with the oesophageal, gastric and CRC. A bacterial infection such as Helicobacter pylori increases the risk of developing gastric cancer.…”
Section: Review Articlementioning
confidence: 99%